A validated, precise TLC-densitometry method for simultaneous quantification of mahanimbine and koenimbine in marketed herbal formulations - Nabarun Mukhopadhyay; Rezwan Ahmed; Kajal Mishra; Rujuta Sandbhor; Ram Jee Sharma; Venkata Rao Kaki (SpringerOpen, 2024)
Abstract Background Murraya koenigii (L.) Spreng. (Rutaceae) is an important medicinal plant in natural products research for its diverse pharmacological activities. Carbazole alkaloids were the major classes of phytoconstituents obtained from different parts of this plant, such as leaves, stems, and roots. Mahanimbine and koenimbine are two important carbazole alkaloids obtained from the M. koenigii plant and are known for their anti-cancer, anti-oxidant, anti-diarrhoeal agents, etc. Standardization plays a vital role in the herbal drug industry for maintaining the quality, purity, safety, and efficacy of herbal formulations, and hyphenated analytical techniques like HPTLC, HPLC, GC-MS, and LC-MS were utilized for this purpose. In the present study, a specific, simple, and rapid semi-automated TLC method was developed to quantify mahanimbine and koenimbine in some marketed herbal formulations, and the same was validated based on (ICH)-Q2-(R1) guidelines. Results This study revealed that the powder formulation (F3) contains the highest amount of mahanimbine (62.32 µg), but the tablet formulation (F1) contains both mahanimbine (41.19 µg) and koenimbine (143.6 µg). Conclusion A simple, specific, and reproducible semi-automated TLC method was developed and validated successfully as per (ICH)-Q2-(R1) guidelines and can be utilized for analysing marketed herbal formulations containing M. koenigii powder/extracts.